The Effect of Project-Based Learning Method InImproving Students’ English Speaking Skills - Dewi, Sistri Kartika; Susanto, Ferri; Anita (Fakultas Sastra - Universitas Muslim Indonesia, 2025)
This research aims to determine the effect of the Project Based Learning (PjBL) method on improving students’ English speaking skills at SMPN 16 Bengkulu City. This study employed a quantitative approach using a quasi-experimental design with a non-equivalent control group. The sample consisted of two seventh-grade classes: class VII G as the experimental group and class VII B as the control group, with a total of 62 students. The instrument used was a speaking test assessing three components: fluency, accuracy, and comprehensibility. The research procedures included a pre-test, four treatment sessions for the experimental group, and a post-test. The results indicated a significant improvement in speaking skills among students taught using the PjBL method. The experimental group’s mean score increased from 35.8 (pre-test) to 66.9 (post-test), while the control group increased from 34.3 to 55.7. Normality and homogeneity tests showed that the data were normally distributed and homogeneous. The independent sample t-test result revealed a significance value lower than 0.05, indicating that PjBL had a statistically significant effect on students' speaking achievement. In conclusion, the Project Based Learning method is effective in enhancing students’ English speaking skills, particularly in fluency, accuracy, and comprehensibility. It is recommended that English teachers apply PjBL as an interactive, student-centered learning strategy.